Prevalence of thyroid disorders in pregnant Arab women: A systematic review and meta-analysis - Ahmad B. Aamir; Rabia Latif; Hoor H. Alqudihi; Roaa A. Zedan; Sarah Hunachagi (Journal of Family and Community Medicine)
Since thyroid profile is linked to genes and differing environmental factors, it is essential to evaluate the frequency of thyroid diseases in various ethnicities. The aim of this systematic review and meta-analysis is to explore the pooled prevalence of thyroid disorders in pregnant Arab women. Following the prospective registration (PROSPERO CRD42024590477), four databases (PubMed, Scopus, Web of Science, and Cochrane) were searched systematically to retrieve studies that report the prevalence of thyroid hormone disorders in pregnant Arab women. Data were synthesized using RStudio within a random effect model. Study heterogeneity and data robustness were assessed by I2 and sensitivity analysis, respectively. Egger’s regression asymmetry test and funnel plots were used to explore publication bias. Search results yielded 981 studies from which nine studies were taken. The risk of Bias was “high” in one, “moderate” in five and “low” in three studies. The estimated pooled prevalence were: subclinical hypothyroidism (SCH) 20% (95% confidence interval [CI]: 14%–28%) (I2 = 94%, P < 0.01), overt hypothyroidism (OH) 3% (95% CI: 1%–8%) (I2 = 79%, P < 0.01), isolated hypothyroxinemia (IH) 4% (95% CI: 2%–6%) (I2 = 69%, P = 0.02), unspecified hypothyroidism 27% (95% CI: 10%–45%) (I2 = 98%, P < 0.01), and hyperthyroidism 2% (95% CI: 1%–3%) (I2 = 0%, P = 0.45). No significant publication bias was detected (Egger regression asymmetry test P values; SCH = 0.10; OH = 0.16; IH = 0.62; hyperthyroidism = 0.15). Study showed that in pregnant Arab women, unspecified hypothyroidism is more prevalent than hyperthyroidism. Of the subcategories of hypothyroidism, SCH is the most prevalent followed by IH and OH.